GAMBARAN ASUPAN MAKAN PASIEN DIABETES MELLITUS TIPE II DENGAN KADAR GLUKOSA DARAH PADA PASIEN RAWAT JALAN DI RSUD Dr. MOEWARDI - ARVIANI, DEVITA, Endang Nur W, S.St., M.Si.Med, Elida Soviana, S.Gz., M.Gizi (2015)
Background: Diabetes mellitus (DM) is the drove indication that appear in certain person who experience in raising blood glucose contain caused by less absolute insulin deficiency in absolute and relative (Rusmiah, 2011). Diabetes mellitus experince from 8.4 million in 2000 to be around 21.3 million in 2030 in Indonesia country. The second type of Diabetes mellitus type II is strongly influenced by the intake of eating so to medical therapy should be may the controll glucose. One of the most important for patient is manage diabetes mellitus are control of blood glucose levels. Objective: To determine food intake of patients with blood glucose levels to the second type of diabetes mellitus treatment outpatients in RSUD Dr. Moewardi Methods: This research is an observational descriptive research with cross sectional approach. The samples of the reseach is the patients of with type II diabetes mellitus outpatients in RSUD Dr. Moewradi. Results: The research use 55 sampleies . The intake consumption samples has sequent 49 samples of energy cinsumtion with 89% prevalence, 55 sample of protein consumstion with 100% prevalence. 47 samples of fat comsumtion with 85,4% prevslence and 39 samples of carbohidrate sonsumtion with 70.9% prevalence. Conclusion: The food consumtion ilustration of type II diabetes mellitus is good category that normal glukose level is 18.8% low comsumtion category with abnormal glukose level is 78.1%